Nitisastra Sebagai Pedoman Seorang Pemimpin Membina Generasi Muda Sekaa Teruna - Dwyq Saputra, I Kadek Bharata (Jayapangus Press, 2022)
The purpose of this study was to describe the teachings of nitisastra as a guide for a leader to foster the young generation of sekaa teruna. The method used in this research is descriptive qualitative research. In Bali, the Hindu community knows the teachings of Nitisastra as Kakawin Nitisastra, Kakawin Nitisastra contains the science of leadership that can be used or applied to community life and the education system. Certain figures often associate Nitisastra's teachings with political science, and not a few also figures that Nitisastra is a science of leadership. Leadership is an ability that is owned by someone where a person is able to coordinate and communicate with members. The progress of a leader can also be measured from his guidance to young generation sekaa teruna. Given that the young generation is the spearhead of a country's progress, future of the country is determined by its young generation. Therefore, every young man, especially in Indonesia, who is still a student, has reached the student seat or has completed education is an important factor that is highly relied on by a leader and nation in realizing the ideals of the nation and then maintaining the integrity of the nation. Therefore, Leaders who can train executives young cadres is needed for a better purpose for the future development of the nation.